ANALYSIS OF FACTORS WHICH AFFECTING THE RETURN ON ASSETS IN FISHING INDUSTRY WHICH PRODUCING RAW MATERIALS LISTED IN INDONESIA STOCK EXCHANGE - Vemy Mustika; Agus Tjahjono; Wahyu Handayani (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2016)
The company will do many activities to achieve the main objective of obtaining profits. The company's ability to earn profits is called profitability. In this study profitability accounted by Return on Assets (ROA). The study done on a fishing company listed on the Indonesia Stock Exchange (BEI). The research objective was to determine the profile of the company, analyze the influence of Current Ratio (CR), Net Profit Margin (NPM) and Firm size (Size) simultaneously and partially on ROA, and analyze which dominant variables influence on ROA. Methods of data analysis was done by calculating CR, NPM, size and ROA, classic assumption test, multiple linear, adjusted R2 test and test hypotheses. PT. Chentral Proteinaprima fisheries aquaculture company in Indonesia with the highest firm size value, PT. Dharma Samudera Fishing Industries is a company of marine fisheries with the highest ROA value, PT. Inti Kapuas International is a company of Arowana fish breeding with the highest value of CR and NPM. CR, NPM, and size together affect the ROA. CR has negative effect on ROA. NPM has positive effect on the influence of ROA. While size does not affect on ROA. NPM is the dominant from the three factors. Companies should be able to increase net income and must be able to maintain the value of CR that is not too high. Keywords: ROA, CR, NPM, firm size, BEI